HUBUNGAN ANTARA PERSEPSI DUKUNGAN ORGANISASI (PERCEIVED ORGANIZATIONAL SUPPORT) DENGAN KETERIKATAN KARYAWAN - Mujiasih, Endah (Jurnal Psikologi, 2015)
Employee participation is essential for the effectiveness of the organization. The employees mentioned are not only reliable but also loyal, committed, and willing to contribute better performance, or in other words, employees with employee engagement. Employees having high level of engagement are able to help the adaptation of the organization to the surrounding communities. The research was aimed to determine the correlation between perceived organizational support and employee engagement. Data collection was conducted based on Perceived Organizational Support Scale/POS (Î± = .931) and Employee Engagement Scale (Î± = .903).Â The hypothesis of the research was the more positive perceived organizational support results in the higher employee engagement. Data were analyzed using simple regression. The result shows a positive correlation between perceived organizational support and employee engagement (r = .631; p < .001). It means that the hypothesis has been accepted. In the research, POS contributed effectively as much as 39.8% to employee engagement.